Encountering Ethical Issues in a Sensitive Case Study Research: A Qualitative Exploration of the Victimized Ahmadiyya Minority in Indonesia - Regus, Maksimus (Institut Filsafat dan Teknologi Kreatif Ledalero, 2024)
This article examines the importance of understanding ethical dilemmas in social research on sensitive topics. The paper is elaborated and presented based on the literature review and experiences in sensitive research. This article summarizes ethical issues, the Ahmadiyya case as a sample of a sensitive topic, ethical dilemmas, their resolutions, and lessons learned. This article reflects on the opportunities for fluent analysis in a sensitive case. This article is an introductory study of the ethical dilemma in analyzing a sensitive issue. Keywords: Indonesia, the Ahmadiyya Group, Violence, Ethical Dilemma, Sensitive Research